Service Quality, Customer Satisfaction, Trust on Consumer Value Perceptions in Online Shop Bedukmutu UMY - Sanusi, Anwar (Interdisciplinary Social Studies, 2022)
Bedukmutu stands for purchases of quality Muhammadiyah products. Bedukmutu is an online buying and selling tool or system developed to manage economic potential at UMY. The presence of Bedukmutu was initiated by Dr. Suryo Pratolo, M.Si., Akt., lecturer at the Faculty of Economics and Business, UMY, since April 2017. The main purpose of the establishment of Bedukmutu is to manage Muhammadiyah's independence in the economic field, in accordance with the mandate of the 47th Muhammadiyah congress in Makassar, 2015.  Bedukmutu can be accessed at Bedukmutu.jualretail.com. This study aims to determine the effect of service quality, satisfaction, consumer trust on the perception of consumer value at the Bedukmutu UMY online store with a moderating variable in the form of corporate image. To test the hypotheses, the researcher used data collected through a questionnaire with a total of 400 respondents using the Random Sampling technique and statistically analyzed using Structural Equation Modeling (SEM) and assisted by the AMOS 24 program. The results showed that service quality on perceived value with the moderating variable of corporate image was positive, meaning that the higher the influence of service quality moderated by corporate image, the higher the perceived value generated.